Development of a Soundproof Device for 950 Watt rated Portable Generators - Musa Nicholas Akhaze; Enoch John (Journal of Applied Sciences and Environmental Management)
The noise emanating from generators has adverse effects on our health. In view of this, this paper reports  the development of soundproof device for 950Watt rated generators which are widely used portable  generators. Performance evaluation of the soundproof device was carried out, and the sound pressure level  of the generator was reduced by 7.64, 6.24, 6.82, 8.72 and 8.68dB at distances of 0.70, 1.40, 2.10,  2.80 and 3.50m from the generator respectively. © JASEM